No espaço-tempo da brincadeira no Programa Curumim/SESC São Carlos : crianças e adultos, saberes em relação - Sartori, Gabriela Dias (2016)
This research seeks to comprehend the play, present in childhood ludic culture, in the wide context that involves child and its stories, social cultures and with those, the educative processes that are produced. The study subjects were forty-two child, between 7 and 12 years old, that participated in Programa Curumim and invited me to play and/or talk with them in the free time. This research sets out to comprehend how children organize and experience their play in the "free time" on Programa Curumim, as well to compehend the relation between the researcher with children, inside this play environment. The research question that guides this study was: What objectives and subjectives conditions, allow the emergency and experience of play in Programa Curumim, particularly in the "free time"? The data collect was made through nonstructured observation, participant observation and field diary. The methodology of this work is based on qualitative reasearch principles, by which, the experience and flexiblity are elements appreciated. This research seeks to contribute to Education area with discussions about the importance of the play, the relations that emerge from those moments and elements of childhood ludic culture that are present in the educative processes built, having as an axis humanizing processes.